Prevalence of coronary artery disease and its associated risk factors in Aljouf region of Saudi Arabia (Bangladesh Journal of Medical Science, 2022)
Objective:Toevaluate the prevalence of coronary artery disease (CAD) with its associated risk factors among Saudi population in Aljouf, Sakaka, Saudi Arabia.Methods: This is a retrospective hospital based study conducted at King Abdul Aziz specialized hospital Sakaka Aljouf, Saudi Arabia by selecting participants with diagnosed CAD by coronary angiogram, the meanage 55.1 ± 10.8 yrs ( range 35-75-years)over a period ofJanuary 2019to December 2019. Demographic characteristics included age, sex,diabetes, hypertension, smoking and family history of CAD. Laboratory data included such as total cholesterol, triglyceride, LDL and HDL levels. Collected data were analyzed by using SPSS 20.00software.Results: One hundred two participants, out of eight hundred fifty five were diagnosed CADwhich included 64.7% stable angina and 35.2% unstable angina. The total prevalence of CAD obtained from this study was11.9% among male and female was7.89% and 4.621% respectively (P